Suatu Telaah terhadap Metode Ferrari untuk Menentukan Akar dari Persamaan Kuartik - Amelia, Mona (Journal of Mathematics UNP, 2025)
A polynomial equation with the highest power of four is called a quartic equation, which has the general form. A common problem with equations is finding the roots, that is the values of that satisfy the equation. This research aims to determine the roots of quartic equations analytically using the Ferrari method. The steps involved are reviewing the method, analyzing the graph and characteristics, determining the roots of the quartic equation, and forming a formula with the characteristics of the roots of the quartic equation. The results show that the reduced quartic equation is the fundamental form for solving equations using the Ferrari method. The roots of the reduced quartic equation are decomposed into five cases and the characteristics of the roots of the quartic equation are obtained based on the values.